Fixing the Eschatological Scales: Judgement of the Soul in Late Medieval and Early Modern Irish Tradition - Ryan, Salvador (Studies in church history, 2009)
The Annals of Loch Cé, a native Irish chronicle compiled in north Roscommon in the years 1588-9, contains the following entry for the year 1568: A cold, stormy year of scarcity was this year; and this is little wonder, for it was in it Mac Diarmada died, i.e. Ruaidhrí, the son of Tadhg, the son of Ruaidhrí Óg, i.e. king of Mag-Luirg and Airtech and Tir-Tuathail and chief lord over the whole territory of Clann-Maelruanaidh, and some more of the districts and fair territories of Connacht…